2010
DOI: 10.1002/ajp.20872
|View full text |Cite
|
Sign up to set email alerts
|

Lemurs in a complex landscape: mapping species density in subtropical dry forests of southwestern Madagascar using data at multiple levels

Abstract: The study of southern dry forest lemurs has been largely restricted to small reserves; yet, the majority of the region's lemur populations reside outside protected areas. Lemur catta and Propithecus verreauxi occupy the same forests but have different dietary preferences. This study assessed L. catta and P. verreauxi population densities across a 3-km dry forest gradient (1,539 ha) in southern Madagascar. The study was designed to allow lemur densities to be related to particular forest types. A particular aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 62 publications
2
34
0
Order By: Relevance
“…As others have noted, ring-tailed lemur densities appear to be correlated with Tamarindus abundance in gallery forests [Gould et al, 2003;Blumenfeld-Jones et al, 2006], and their density has been found to be higher along the river in P1 [Axel and Maurer, 2010]. Similarly, the majority of the plant species in table 1 eaten by sifakas are found in the western half of P1 and in P2 [Yamashita, 2002], which coincides with their higher densities in those locations [Axel and Maurer, 2010].…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…As others have noted, ring-tailed lemur densities appear to be correlated with Tamarindus abundance in gallery forests [Gould et al, 2003;Blumenfeld-Jones et al, 2006], and their density has been found to be higher along the river in P1 [Axel and Maurer, 2010]. Similarly, the majority of the plant species in table 1 eaten by sifakas are found in the western half of P1 and in P2 [Yamashita, 2002], which coincides with their higher densities in those locations [Axel and Maurer, 2010].…”
Section: Discussionmentioning
confidence: 52%
“…Parcel 1 (P1) is the 80 ha deciduous tropical dry forest [Sussman and Rakotozafy, 1994] where the majority of research on lemurs at BMSR has taken place. Parcel 2 (P2) is a 520 ha plot located 5 km to the west of P1 and is composed of a patchwork of dry, deciduous forest and spiny forest [Axel and Maurer, 2010] ( fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The research goal was to document lemur habitat use in both protected (Beza Mahafaly Special Reserve) and nonprotected areas in the vicinity of the reserve. Axel and Mauer [2011] found that Lemur catta (ring-tailed lemurs) occurred at highest densities in the gallery forests of the reserve. Population density of Propithecus verreauxi (sifakas) was lower but more uniform across a wide swath of drier forests.…”
Section: Past Present and Future Primate Ecosystemsmentioning
confidence: 99%
“…Also in this issue, Axel and Mauer [2011] used satellite imagery to classify forest types and point transect sampling to document habitat preferences and group size variation in two species of diurnal lemurs currently inhabiting southwestern Madagascar. The research goal was to document lemur habitat use in both protected (Beza Mahafaly Special Reserve) and nonprotected areas in the vicinity of the reserve.…”
Section: Past Present and Future Primate Ecosystemsmentioning
confidence: 99%
“…1 ). Specifically, there is dramatic deforestation and evidence of livestock grazing throughout P2, yet numerous lemur troops live here [Axel and Maurer, 2011]. P2 ring-tailed lemurs have only recently been habituated to humans and thus their health status was previously unknown.…”
Section: Study Site and Speciesmentioning
confidence: 99%